2008
DOI: 10.1242/jcs.021584
|View full text |Cite
|
Sign up to set email alerts
|

Chemical genetic analysis of the regulatory role of Cdc2p in theS. pombeseptation initiation network

Abstract: The protein kinase Cdc2p is the master regulator of cell cycle progression in the fission yeast Schizosaccharomyces pombe. It is required both for entry into mitosis and for onset of DNA replication. Cdc2p must be inactivated to permit exit from mitosis, licensing of replication origins and cytokinesis. To study the role of Cdc2p in greater detail, we generated a cdc2 allele that is sensitive to an inhibitory ATP analogue. We show that the inhibitor-induced cell cycle arrest is reversible and examine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 103 publications
2
77
0
2
Order By: Relevance
“…Our work confirms and extends previous work (17) showing that Clp1 dampens Cdk1 activity by dephosphorylating and inactivating Cdc25. Clp1 facilitates proper contractile ring dynamics and timely cytokinesis by antagonizing Cdk1 phosphorylations that negatively regulate the septation initiation network (SIN) and antagonize contractile ring formation (26,(32)(33)(34)(35). Our data show that abrogation of Clp1-Cdc25 feedback reduces the abruptness of cytokinesis.…”
Section: Discussionmentioning
confidence: 75%
“…Our work confirms and extends previous work (17) showing that Clp1 dampens Cdk1 activity by dephosphorylating and inactivating Cdc25. Clp1 facilitates proper contractile ring dynamics and timely cytokinesis by antagonizing Cdk1 phosphorylations that negatively regulate the septation initiation network (SIN) and antagonize contractile ring formation (26,(32)(33)(34)(35). Our data show that abrogation of Clp1-Cdc25 feedback reduces the abruptness of cytokinesis.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, the data presented here and in previous studies clearly indicate that PP2A (directly or indirectly) inhibits the SIN, which is required for cytokinesis, the last step in the cell cycle. The reason for this difference in organization is unclear; however, we note that the SIN is inhibited by mitotic CDK (Dischinger et al 2008), so it is possible that the regulatory elements coordinating mitosis and cytokinesis are organized differently in S. pombe. For example, other phosphoprotein phosphatases, such as Flp1p/Clp1p and PP1 complexes may be more important for mitotic exit than PP2A.…”
Section: Pp2a and Sin Signalingmentioning
confidence: 89%
“…Analysis of the localization of SIN proteins and their activity in mutant backgrounds has led to the proposition that the order of action of the SIN proteins in the mitotic cell cycle is Cdc7p-Spg1p, then Sid1p-Cdc14p, and finally Sid2p-Mob1p (Sparks et al 1999;Guertin et al 2000). Active Cdc2p inhibits the SIN early in mitosis, and CDK inactivation is required for septum formation (Yamano et al 1996;He et al 1997;Guertin et al 2000;Chang et al 2001;Dischinger et al 2008).…”
Section: Septation Initiation Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition is inhibited by an active SAC. Previous studies have shown that Cdc2p inactivation promotes the transition to the asymmetric state of the SIN (Chang et al, 2001;Dischinger et al, 2008;Yamano et al, 1996), suggesting that the SAC effect results from delayed inactivation of Cdc2p.…”
Section: What Regulates the Early-late Transition?mentioning
confidence: 96%